The day of the Djinn warriors / #4. - Kerr, Philip (Kerr, Philip. Children of the lamp, 2008)
Twins John and Philippa Gaunt set out on a dangerous journey around the world as they race to save their mother from her destiny as the Blue Djinn of Babylon, their father from a curse, and museums from a series of strange hauntings and unexplained robberies, and, in the course of their travels, discover an evil force that is is filling the world with wicked spirits.